Inside Cover: Evaluation of tert‐Butyl Isosteres: Case Studies of Physicochemical and Pharmacokinetic Properties, Efficacies, and Activities (ChemMedChem 3/2015). Issue 3 (March 2015) - Westphal, Matthias V.; Wolfstädter, Bernd T.; Plancher, Jean‐Marc; Gatfield, John; Carreira, Erick M.
<x xml:space="preserve">Abstract</x> The inside cover picture shows the tert‐butyl group, a common motif in small‐molecule therapeutics, and four potential isosteres: trifluoromethyl, pentafluorosulfanyl, bicyclo[1.1.1]pentyl and cyclopropyltrifluoromethyl. The effects of the various groups on important physicochemical properties, such as solubility, metabolic stability, and membrane permeability, were investigated in two series of drug analogues allowing for their direct comparison. For further details, see the Full Paper by Erick M. Carreira et al. on p. 461 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>